Transitional particle swarm optimization - Nor Azlina, Ab. Aziz; Zuwairie, Ibrahim; Marizan, Mubin; Sophan Wahyudi, Nawawi; Nor Hidayati, Abdul Aziz (Institute of Advanced Engineering and Science (IAES), 2017)
A new variation of particle swarm optimization (PSO) termed as transitional PSO (T-PSO) is proposed here. T-PSO attempts to improve PSO via its iteration strategy. Traditionally, PSO adopts either the synchronous or the asynchronous iteration strategy. Both of these iteration strategies have their own strengths and weaknesses. The synchronous strategy has reputation of better exploitation while asynchronous strategy is stronger in exploration. The particles of T-PSO start with asynchronous update to encourage more exploration at the start of the search. If no better solution is found for a number of iteration, the iteration strategy is changed to synchronous update to allow fine tuning by the particles. The results show that T-PSO is ranked better than the traditional PSOs.